2008
DOI: 10.1080/09638230701498366
|View full text |Cite
|
Sign up to set email alerts
|

Adults traumatized by child abuse: What survivors need from community-based mental health professionals

Abstract: Aims: To understand, from the ''insider'' perspectives of adults abused as children, the aspects of community mental health interventions that are experienced as helpful and less helpful after discharge from inpatient trauma treatment. Method: In-depth interviews were conducted with 30 child abuse survivors, six months after discharge from a specialized trauma treatment program. Results: Participants reported difficulties managing intense feelings that surfaced after inpatient treatment, which became more prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Overcoming patient ambivalence for trauma processing and having a safe and trusting environment during treatment was discussed by Shearing and colleagues [ 35 ], who investigated patient views on reliving the trauma as part of their PTSD treatment. Of interest, the results of this study were similar to that of other studies which included treatments with a stabilisation phase or as part of a group program, suggesting that the same treatment components and difficulties exist regardless of the inclusion of a phase-based approach [ 36 , 37 ]. One argument for phase-based treatments is that they help reduce patients’ fears and promote their receptivity to trauma processing [ 38 ].…”
Section: Discussionsupporting
confidence: 77%
“…Overcoming patient ambivalence for trauma processing and having a safe and trusting environment during treatment was discussed by Shearing and colleagues [ 35 ], who investigated patient views on reliving the trauma as part of their PTSD treatment. Of interest, the results of this study were similar to that of other studies which included treatments with a stabilisation phase or as part of a group program, suggesting that the same treatment components and difficulties exist regardless of the inclusion of a phase-based approach [ 36 , 37 ]. One argument for phase-based treatments is that they help reduce patients’ fears and promote their receptivity to trauma processing [ 38 ].…”
Section: Discussionsupporting
confidence: 77%
“…Both have been identified as key desirable outcomes in the treatment of trauma (Pfeiffer et al, 2014;Snedden, 2012). Studies have suggested that without continued community support and a trauma-informed approach to IJOT 48,1 recovery, the benefits of resource-intensive trauma treatment programmes may not be effectively retained in the long term (Felitti and Anda, 2010;Harper et al, 2006Harper et al, , 2008Parker et al, 2007). Parker et al (2007) shed light on this potential, which lies beyond the amelioration of traumatic stress symptoms.…”
Section: Implications For Practicementioning
confidence: 99%
“…Despite this, providing ongoing community therapeutic support, including a spiritual/meaning-making component (Harper et al, 2006;Parker et al, 2007), may be areas worthy of exploration by occupational therapy. These are themes which resonate with the profession's inherent philosophy and practice (Harper et al, 2006(Harper et al, , 2008. Occupational therapy resources, such as the Canadian model of occupational performance and engagement (Townsend and Polatajko, 2007), which are person-centred and inclusive of a "spiritual meaning making" component may provide the supportive framework upon which to base investigation and practice in the future.…”
Section: Implications For Practicementioning
confidence: 99%
“…2005), treatment, and recovery (Harper et al . 2008; SAMSHA 2014). Trauma Informed Care (TIC) is an approach to service delivery, which requires clinicians and organizations to consider that all individuals who access their services may have experienced trauma and that experiences of mental illness and treatment can also be traumatic (Bateman et al .…”
Section: Introductionmentioning
confidence: 99%
“…Trauma is a broad term used to encompass adversity, toxic stress or exposure to harmful events, acts, experiences, or dynamics. Trauma is known to be highly prevalent in the lives of people who access mental health services (Cusack et al 2006;Mueser et al 2004) with exposure to trauma understood to impact upon lifetime health (Anda et al 2006;Felitti et al 1998), as well as experiences of mental illness (Brand et al 2017;Read et al 2005), treatment, and recovery (Harper et al 2008;SAMSHA 2014). Trauma Informed Care (TIC) is an approach to service delivery, which requires clinicians and organizations to consider that all individuals who access their services may have experienced trauma and that experiences of mental illness and treatment can also be traumatic (Bateman et al 2013;Harris & Fallot 2001;Isobel & Edwards 2017).…”
Section: Introductionmentioning
confidence: 99%